Reliability of Functional Movement Screen and sexual differentiation in FMS scores and the cut-off point among amateur athletes - Domaradzki, Jarosław; Koźlenia, Dawid (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Functional Movement Screen (FMS) is a tool usedin injury prediction based on the quality of movement patterns.Crucial is to determine the cut-off point which indicates theinjury risk increment. Most of the researches regard professionalathletes. Aim of Study. The aim of this study was to determinethe reliability of the FMS test, and sexual differentiation in thevalue of the FMS total score test and subtests. Furthermore, thestudy aimed to evaluate the values of injury risk cut-off pointin the FMS test in young male and female individuals from themoderately-active population. Material and Methods. The studygroup consisted of 89 physically active individuals not involvedin high-performance sport: 42 males aged 20.5 ± 1.10 years,and 47 females aged 20.0 ± 0.68 years. FMS, a questionnaireconcerning the previous injury history of 12 months precedingthe study were used. The interclass correlation coefficient(ICC) was used to evaluate the reliability of the FMS test anda receiver operating characteristic curve (ROC) for FMS cut-offscores was calculated. Results. The FMS test showed excellentagreement between two screenings. There were some differencesin the quality of movement patterns between men and women insubtests. The values of injury risk cut-off scores were differentbetween sexes, 14 points for males and 17 points for females.Conclusions. The FMS test is a highly reliable research tool.For the average population of physically active young male andfemale amateur athletes, the cut-off score values in the FMStest should be evaluated separately between sexes to determineinjury risks.
Keywords: FMS test reliability; cut-off score; physical activity